(untitled) (INNOVATIVE ECONOMY, 2020)
Pecheniuk A.P. TOURIST POVERTY AS A CULTURAL AND HUMANITARIAN DETERMINANT Purpose. The aim of the article is improvement and complementation of theoretical aspects of the study of tourist poverty. Methodology of research. The following methods are used during the study: comparison - to determine the dynamics of outbound and domestic tourist flows of our state; systematic approach - when considering tourism poverty as a system that consists of a certain number of interrelated elements of both material and cultural-humanitarian nature and comprehensively influences the effectiveness of tourism development of the country; scientific abstraction - with the isolation in the phenomenon under study of a strong, stable, typical connection, which allowed to form in a generalized way the characteristic features and to determine the problems of cultural and humanitarian development. Findings. Tourist poverty of the population has been investigated for the purpose of revealing the connection with the educational sphere and with the sphere of cultural and humanitarian development of citizens. It is established that tourist poverty is not only related to material aspects, and requires close interaction with the educational environment. It has been proven that the result of tourist poverty is the tourist marginalization of the population. The characteristic features of tourist poverty from the point of view of material and worldview characteristics are highlighted. The problems of cultural development have been identified and the causes of cultural deconsolidation of society and the formation of tourist poverty have been identified. The ways of strengthening of unity in the society and overcoming the humanitarian-cultural tourist poverty are proposed. Originality. The author defines the concept of "tourist marginalization" - a process of reducing tourist activity due to economic and humanitarian factors, characterized by an increase in the number of citizens who do not participate in tourist activities, are socially passive, does not position itself with certain social groups, without clear identification groups or tourist interests that are included in tourist consumption due to media background agents. Practical value. The results of the study can be used to develop an effective national strategy for the cultural, humanitarian and tourism development of the state, which will ultimately prove to be a significant social effect. Key words: tourist poverty; social inequality; cultural and humanitarian development; cultural competence; cultural deconsolidation.